Effectiveness of Chest Physiotherapy toward Tuberculosis (TBC) Patient to Overcome Ineffective Airway Clearance in Dieng Inpatient Room of dr. Abdoer Rahem Hospital Situbondo: A Case Report - RA. Arsyifa Nanda Fedora; Rondhianto; Siswoyo; Mohammad Shodikin (Health and Technology Journal (HTechJ), 2024)
Tuberculosis is an infectious and potentially fatal disease in worldwide, caused by lungs inflammation due to Mycobacterium bacteria infection. Tuberculosis patient experiences coughing with phlegm, shortness of breath or dyspnea, accumulation of exudate or sputum. Excessive of sputum accumulated can lead to obstruction of breath way and increase lungs infection that related to ineffective airway clearance. Chest physiotherapy can be intervention of nursing to overcome ineffective airway clearance that helps in clearing accumulated sputum and improving oxygen saturation. This scientific work uses a case report method that describes the case of Tuberculosis patient with main problem of nursing that was called ineffective airway clearance. The sampling was consecutive sampling but only one patient included in the case. The sample of study was Mrs. M, 32 years old who had Tuberculosis patient with ineffective airway clearance. The research was conducted twice daily for 3 days began from December 21st, 2023, to December 23rd, 2023, in the Dieng Inpatient Room of dr. Abdoer Rahem Hospital Situbondo. Intervention was done in two sessions, that were morning and afternoon. Based on observations, there was no significant difference on blood pressure level, but there were decreasing pulse rate, decreasing respiratory rate, increasing oxygen saturation value, and improving ability of sputum production post intervention Chest Physiotherapy on the third day. The application of Chest Physiotherapy quietly helped in expelling phlegm and improving respiratory status.